Climate variability and household welfare in northern Ghana - Paul Kwame Nkegbe; Naasegnibe Kuunibe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Climate variability poses a major risk to agricultural incomes in Africa. In Ghana, most of the country's poor people live in the north and households find it difficult to hold back their productive assets during the lean season. This study investigates the impact of climate variability on household welfare in the area using a three-period panel data from the Ghana Living Standards Survey, in addition to data on annual rainfall and temperature for northern Ghana for the period 1991 to 2007. Using trend equations and the Ricardian approach to analyze the data, the results show rainfall exhibits a decreasing trend in all regions in the north of Ghana while temperature oscillates, with higher amounts of rainfall and moderate temperatures found to be significant drivers of improved welfare. The study thus concludes that climate variability negatively impacts household welfare, agricultural income, and farm revenue, and recommends inter alia households' diversification of economic activities into areas not directly affected by the vagaries of the climate.
Keywords: I31; Q12; Q54; 330; climate variability; panel data; welfare; individual heterogeneity; Ghana